Propaganda on the American Home Front : The Driving Force of Mobilization - Serrano, Jonathan (The Toro Historical Review, 2020)
This paper explores the impact of propaganda filled mediums and their relationship to the mobilization of predominantly women and children on the American home front during World War II. Primary sources such as posters, pamphlets, films, and booklets were used as evidence to demonstrate how propaganda consumed many aspects of American life to support the war effort. This paper also explores the effectiveness of these propaganda filled mediums while also acknowledging that other factors such as economic-based were also of great importance in the mobilization of many people.